5: LOCAL ENDOSCOPIC RESECTION IS INFERIOR TO GASTRECTOMY FOR EARLY CLINICAL STAGE T1A AND T1B GASTRIC ADENOCARCINOMA: A PROPENSITY-MATCHED STUDY. (23rd April 2022) - Kamarajah, S; Markar, S; Phillips, A; Salti, G; Dahdaleh, F
Abstract: Background and aim: The role of ER in the management of subsets of clinical T1N0 gastric adenocarcinoma remains controversial. The aim of this study was to evaluate the outcome of endoscopic resection (ER) versus gastrectomy in node negative cT1a and cT1b gastric adenocarcinoma. Methods: Data from the National Cancer Database (2010–2015), was used to identify patients with clinical T1aN0 (n = 2, 927; ER, n = 1, 157; gastrectomy, n = 1, 770) and T1bN0 (n = 2, 915; ER, n = 474; gastrectomy, n = 2, 441) gastric adenocarcinoma. Propensity score matching (PSM) and Cox multivariable analyses were used to account for treatment selection bias. Results: ER for cT1a and cT1b cancers was performed more frequently over time. Rates of node-positive disease in patients with cT1a and cT1b gastric adenocarcinoma were 5% and 18%, respectively. In the matched cohort, gastrectomy was associated with increased survival compared to ER for cT1a cancers (HR: 0.79, 95% CI: 0.66–0.95, P = 0.013), and corresponding 5-year survival for gastrectomy and ER were 72% and 66% ( P = 0.013), respectively. For cT1b cancers, gastrectomy had a significantly longer survival compared to ER (HR: 0.77, 95% CI: 0.63–0.93, P = 0.008) and the corresponding 5-year survival for gastrectomy and ER were 60% and 50% ( P = 0.013), respectively. Conclusion: This study demonstrates ER inferior long-term survival for clinical T1aN0 and T1bN0 gastric adenocarcinoma, despite current recommendations for ER in cT1 gastric cancers. Future research should seek to identify the subset of T1a and T1b cancers at low risk of nodal metastasis and thus would maximally benefit from ER.